Influence of physiotherapy on forward head posture and related problems – a critical review of literature - Wroński, Zbigniew; Klasic, Mario; Gjinovci, Burim (Physiotherapy Review, 2024)
Forward head posture (FHP) is frequently observed in both patients and the asymptomatic population. FHP is defined as a position in which the external auditory canal is forward to the plumb line that goes through the shoulder. The reasons for these changes can vary, but one contributing factor may be the increased use of modern technology such as smartphones, laptops, and tablets. Studies have shown that individuals using smartphones for more than 4 hours per day are more likely to exhibit FHP and experience neck pain more frequently. A forward head position is associated with lower cervical spine flexion and upper cervical spine extension. The craniovertebral angle (CVA) is commonly used to quantify the degree of FHP. Existing evidence suggests that manual therapy has the potential to influence pain and disability in patients, prompting the research focus on postural changes. Providing patients with information about the possibility of postural corrections through physiotherapy is deemed valuable. A total of six papers were critically reviewed, comprising five randomized controlled trials and one systematic review. In summary, all studies indicate the potential influence of physiotherapy on forward head posture as measured by the craniovertebral angle. Manual therapy appears to be beneficial in the short term, and exercises are deemed necessary to achieve lasting effects of the treatment. The findings suggest that it is indeed possible to influence forward head posture through physiotherapy management.